Synthesis and Characterization of Reduced Graphene Oxide (rGO) Started from Graphene Oxide (GO) Using the Tour Method with Different Parameters - Habte, Adere Tarekegne; Ayele, Delele Worku (Advances in materials science and engineering, 2019)
A new approach to synthesize graphene is oxidizing graphite powder with a mixture of H2SO4/H3PO4 acids and potassium permanganate. Parameters such as reaction time, reaction temperature, and amount of concentration were varied to study the degree of oxidation of graphite to graphene oxide. Currently, an improved method for the preparation of graphene oxide was the most common one. A mixture of H2SO4/H3PO4 (9 : 1 volume ratio) instead of only H2SO4 resulted in increased hydrophilic and oxidized GO without the emission of toxic gas, which differs from the traditional Hummers’ method. The graphene oxide (GO) was converted to reduced graphene oxide (rGO) by chemical reduction using ascorbic acid as the reducing agent. The GO and rGO were characterized by UV-visible spectroscopy, FTIR spectroscopy, and X-ray diffraction patterns. The result showed that treating graphite powder with potassium permanganate (1 : 9) and a mixture of concentrated H2SO4/H3PO4 acids at 50°C for 12 hours resulted in a better oxidation degree. The designed synthesis strategy could be easily controlled and is an alternative green approach for the production of graphene oxide and reduced graphene oxide.